Exploring the diffusion of big data analytics within accounting education / Nur Insyirah Mohamed Sufian ... [et al.] - Mohamed Sufian, Nur Insyirah; Kasim, Eley Suzana; Md Zin, Norlaila; Surtikanti, Surtikanti (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Universities need to ensure that future accountants are well prepared for employment in the Big Data era by incorporating Big Data Analytics (BDA) within their accounting curriculum. The incorporation of BDA into accounting curricula is an innovation that will diffuse over time. By investigating the diffusion of BDA among universities, valuable insights can be gained that can help universities prepare future accountants. However, studies on BDA in accounting education and its diffusion are still limited. Hence, this study aims to explore the diffusion of BDA in accounting education among selected universities in Malaysia. Semi-structured interviews with professors from public and private universities are the main method of gathering data, with document reviews as supplement. A total of eleven educators were interviewed, consisting of eight interviewees from public universities, while the remaining were from private universities. Based on Diffusion Theory of Innovation, the thematic analysis indicates that all selected public universities have progressed in their diffusion stages, while private universities experience little or no diffusion. The insights gained have important implications for policymakers, administrators, and academicians.